Democratic foreign policy making : problems of divided government and international cooperation - Pahre, Robert (Palgrave Macmillan, 2006)
Leading scholars from the United States and the European Union examine how democracies make foreign policy when their citizens disagree about what to do. The authors focus in particular on differences of opinion between the legislature and the executive - often called 'divided government' - and the constraints of public opinion on a leader's actions.